THE LENIN'S SCHOOL CAMPUS AND THE MODERNIZATION OF KABARDIAN AND BALKAR CULTURE - I. H. TKHAMOKOVA (Кавказология)
This article investigates the role of the Lenin's Campus, opened in the city of Nalchik in 1924, in the modernization of Kabardian and Balkar culture. With that, the culture is seen in the widest sense of this word, i.e. includes not only the statement of values or literature and art, but also the material culture, customs and ceremonies. The role of the campus was not only training of specialists, the so-called domestic labor, but also mentoring of "new Kabardians, new Balkars." Beyond playing an important role in elimination of illiteracy, development of the educational system, formation of Kabardian and Balkar literature and art, the graduates of educational institutions of the town were an example of a new lifestyle, new values, new material culture. The Soviet version of cultural modernization was notable for its quick rate and violent methods. The cadets of the Lenin's Campus had not only to give up a great many of the traditional culture values, but also to wage a relentless struggle with them, which, in the long run, ended with the victory of new culture forms.